The Cultural Education of Khataman Al-Quran in Realizing Maluku Society - Sa'idah , Umm; Nursaid , Nursaid (Vifada Journal of Education, 2024)
The Khataman al-Qur'an culture is one of the cultures that is still maintained in Maluku. Each region has a different way of implementing it. This study has revealed how the implementation of the Khtaman al-Qur'an in Maluku, especially Buru Regency, what Islamic educational values are contained in the Khataman al-Qur'an culture, what factors support and hinder the celebration of the Khataman al-Qur'an and how the implications of Islamic educational values in the Khataman al-Qur'an in realizing a society with Qur'anic character. This study uses a qualitative approach. The scope and boundaries of the research area in this study are one of the regencies in Maluku province, namely Buru Regency. This research was conducted from March to October 2022. The informants in this study consisted of 1) the community in the research location area, 2) organizers/committees of the Khataman Al-Quran, 3) traditional leaders, 4) religious leaders, 5) youth leaders, and 6) government officials. The data collection techniques in this study used interviews, focus group discussions (FGD), surveys, observations and documentation . The results of this study are 1). Khataman al-Qur'an in Buru Budaya Regency is carried out in levels. The first level is reading the Qur'an and memorizing short letters from surah ad-Dhuha to surah an-Nas. This is followed by children from kindergarten to elementary school. While the second level is if the students who have finished reading the Qur'an and memorizing per juz are followed by junior high school students and above. The values of Islamic Education contained in the Khataman al-Qur'an culture are 1). The value of Tauhid where the students believe that the book of the Qur'an is the word of Allah that must be read and the values contained therein must be practiced, 2) The value of worship, this is proven by the Khtaman al-Qur'an procession, where the students have demonstrated their reading and memorization in front of their parents and guests, 3). Good moral values, morals towards Allah and morals towards fellow human beings. Factors that support this celebration are: 1). The majority of the people of Buru Island are Muslims who still maintain the Khataman al-Qur'an culture, 2). The existence of a regional government policy or the Regent's Program "GELORA" Bupolo Maghrib Mengaji Movement. While the factors that hinder this activity are: 1). The progress of electronic devices, Hand Phones, children are busy playing HP, 2). Parents' busy work, 3). Cost factors. The implications of the Khataman al-Qur'an cultural values are that students diligently perform the five daily prayers, fast, recite the Koran, say hello, kiss the hands of older people, have good manners towards teachers, parents and others.